Evaluating the Effect of Combined Plant Extracts on α-amylase and α-glucosidase Inhibition Activity as Antidiabetic Agents - Munem, Osama A.; Makky, Essam A.; Tawfiq, Arwa A.; Mahendran, Kasturi; Normaiza, Z. (Science Alert, 2020)
Background and Objective: Diabetes mellitus (DM) is the major health and economic problem through the world. The insufficiencies and severe adversarial special effects related with conventional medicines, led to a strong-minded search for alternative natural antidiabetic agents. The study was aimed to screen the in vitro antidiabetic activity of seven plant extracts. Materials and Methods: The bioactivity of the extracts was correlated through a Gas Chromatography-Mass spectrometry (GC-MS)-based analysis, while extracts with 50% inhibition activity were reported. Results: The α-amylase inhibitory activities of the chloroform extracts of Averrhoa bilimbi, Andrographis paniculata, Eurycoma longifolia and Punica granatum exhibited more than 50% inhibition (50.55, 68.24, 82.42 and 69.73% respectively), while chloroform extracts of A. paniculata, Orthosiphon stamineus and P. granatum exhibited 90.48, 52.00 and 62.00% of α-glucosidase inhibitory effects, respectively. Only ethanolic and methanolic extracts of E. longifolia exhibited α-glucosidase inhibitory effects of 57.80 and 53.31%, respectively. A combination of the ethanolic fraction of E. longifolia with the chloroform fraction of P. granatum at a ratio of 2:1 exhibited the highest α-glucosidase inhibition rate of 148.06%, while a combination of the ethanolic fraction of E. longifolia with the chloroform fraction of O. stamineus at the same ratio exhibited α-glucosidase inhibition rate of 137.43%. A phytochemical analysis based on GC-MS revealed the presence of fatty acids, with palmitic acid recording the highest percentage (100%) in the O. stamineus extract. Conclusion: The observed α-amylase and α-glucosidase inhibitory activities of these plant extracts suggested their potential usage as an alternative sources of antidiabetic agents.